2013
DOI: 10.1088/0031-9155/59/1/219
|View full text |Cite
|
Sign up to set email alerts
|

L-shell x-ray fluorescence computed tomography (XFCT) imaging of Cisplatin

Abstract: X-ray fluorescence computed tomography (XFCT) imaging has been focused on the detection of K-shell X-rays. The potential utility of L-shell x-ray XFCT is, however, not well studied. Here we report the first Monte Carlo (MC) simulation of preclinical L-shell XFCT imaging of Cisplatin. We built MC models for both L- and K-shell XFCT with different excitation energies (15 and 30 keV for L-shell and 80 keV for K-shell XFCT). Two small-animal sized imaging phantoms of 2-cm and 4-cm diameter containing a series of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Recent XFCT work by several groups (Pratx et al 2010, Cong et al 2011, Kuang et al 2013, Kuang et al 2014, Bazalova et al 2014, Ren et al 2014, Feng et al 2014, Ahmad, Bazalova, Xiang and Xing 2014, Ahmad, Pratx, Bazalova and Xing 2014, Sjölin and Danielsson 2014, Bazalova-Carter et al 2015, Ahmad et al 2015) have shown that XFCT can have theoretical molecular sensitivities down to 10 pM for 10 nm diameter AuNPs (Ahmad, Bazalova, Xiang and Xing 2014). Gold concentrations down to 2.5 mg/ml were experimentally detectable with a clinical x-ray source at 14 mGy in a proof of concept setup (Ahmad et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent XFCT work by several groups (Pratx et al 2010, Cong et al 2011, Kuang et al 2013, Kuang et al 2014, Bazalova et al 2014, Ren et al 2014, Feng et al 2014, Ahmad, Bazalova, Xiang and Xing 2014, Ahmad, Pratx, Bazalova and Xing 2014, Sjölin and Danielsson 2014, Bazalova-Carter et al 2015, Ahmad et al 2015) have shown that XFCT can have theoretical molecular sensitivities down to 10 pM for 10 nm diameter AuNPs (Ahmad, Bazalova, Xiang and Xing 2014). Gold concentrations down to 2.5 mg/ml were experimentally detectable with a clinical x-ray source at 14 mGy in a proof of concept setup (Ahmad et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4 Additionally, Manohar et al 5 were able to quantify AuNP concentrations down to 20 mgAu ml 21 in planar images of a 1.2-cm diameter phantom using a bench-top L-shell X-ray fluorescence imaging system. The feasibility of L-shell XFCT has therefore been demonstrated both in silica and experimentally, however, a number of challenges prevent us from introducing L-shell molecular imaging into even the pre-clinical settings.…”
Section: Advantages Of L-shell Xfct Compared With K-shell Xfct Imagingmentioning
confidence: 99%
“…4,5 The size of the pencil beam and the transversal scanning parameters define the spatial resolution of XFCT images. Small beam size and fine scanning steps result in high spatial resolution down to 150 mm, with the expense of long imaging times.…”
Section: Imaging Timementioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20] The pencil beam/single collimated beam from polychromatic x-ray tubes [21][22][23][24][25][26][27] is then used to improve the feasibility of using XFCT; however, this technique requires a long scanning time, e.g., 279 min 28 and 180 h. 29 One important reason for the low efficiency is that using a pencil beam setup requires the beam source to be shifted point by point while measuring a single slice of projection data. Similar processes of shifting on detectors are also required for a fan-beam setup with a single pixel detector.…”
mentioning
confidence: 99%